The Problem of Evil : An Intercultural Exploration - Wawrytko, Sandra A. (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This book is an intercultural exploration of the full scope of evil. The problems of evil have beset humanity throughout the ages and continue to trouble us. The studies here examine evil in Asian thought, in Western theory, in the cosmic order, in human psychology, and in social practice. Insights are added to the philosophical discussions from religion, culture, history, law, technology, and literature.